1999
DOI: 10.1038/sj.bjc.6690489
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cytotoxicity of mitomycin C in human tumour cells with inducers of DT-diaphorase

Abstract: Summary DT-diaphorase is a two-electron reducing enzyme that activates the bioreductive anti-tumour agent, mitomycin C (MMC). Cell lines having elevated levels of DT-diaphorase are generally more sensitive to MMC. We have shown that DT-diaphorase can be induced in human tumour cells by a number of compounds, including 1,2-dithiole-3-thione. In this study, we investigated whether induction of DT-diaphorase could enhance the cytotoxic activity of MMC in six human tumour cell lines representing four tumour types.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 45 publications
(62 reference statements)
2
21
0
Order By: Relevance
“…Treatment of HCT116 cells in vitro with DMF for 48 h increased NQO1 activity in these cells by two-fold (Po0.001), and cells that were pretreated with DMF were 1.4-fold more sensitive to MMC than cells that were not pretreated (Po0.001). This result was similar to our previous findings in murine lymphoma cells (Begleiter et al, 1996) and human breast, lung and colon cancer cells (Doherty et al, 1998;Wang et al, 1999) using synthetic inducers of NQO1.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Treatment of HCT116 cells in vitro with DMF for 48 h increased NQO1 activity in these cells by two-fold (Po0.001), and cells that were pretreated with DMF were 1.4-fold more sensitive to MMC than cells that were not pretreated (Po0.001). This result was similar to our previous findings in murine lymphoma cells (Begleiter et al, 1996) and human breast, lung and colon cancer cells (Doherty et al, 1998;Wang et al, 1999) using synthetic inducers of NQO1.…”
Section: Discussionsupporting
confidence: 93%
“…Cells with elevated NQO1 levels are generally more sensitive to MMC (Begleiter et al, 1989;Marshall et al, 1989;Siegel et al, 1990), and NQO1 can be induced by a wide variety of dietary and synthetic agents (Talalay et al, 1988;Prestera et al, 1993). We have previously shown that NQO1 activity can be selectively increased in tumour cells compared with normal cells, and that this enhances MMC cytotoxicity in human and murine cell lines in vitro (Doherty et al, 1998;Wang et al, 1999). In this study we investigated a novel approach to increasing the antitumour activity of MMC by using a dietary component to selectively induce NQO1 activity in tumour cells compared with normal cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In analogy, PRC compounds may therefore represent a novel class of bioreductive experimental anti-cancer agents that eliminate cancer cells by NQO1-driven redox cycling with induction of apoptosis without imposing the burden of genotoxic alkylating stress observed with conventional bioreductive chemotherapeutic agents [52]. Interestingly, enhanced cytotoxicity of mitomycin C can be achieved in human tumor cells treated with small molecule inducers of NQO1 including sulforaphane and 1,2-dithiole-3-thione [53], and it remains to be seen if NQO1-induction by these classic chemopreventive inducers of phase II detoxification enzymes including NQO1 further sensitizes cancer cells to PRC-induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…We propose the following mechanisms that might explain this individual susceptibility to MMC-related renal toxicity. (a) DT-diaphorase can be induced by a wide variety of compounds, including many dietary substances (Benson et al 1980;O'Dwyer et al 1996;Begleiter et al 1997;Wang et al 1999). For example, rapid induction of this enzyme has been demonstrated in subjects who regularly ingest coffee or broccoli (Sreerama et al 1995).…”
Section: Discussionmentioning
confidence: 99%